Pemberdayaan Perempuan Dan PNPM Mandiri: Kajian Program Pengentasan Kemiskinan Di Kabupaten Ngawi - soerjo, sumiati (Universitas Merdeka Madiun, 2018)
Ngawi Regency in July 2016, the poverty rate is still high, reaching almost 32% of the population. Based on the identification of the location of poverty, it turns out there are 16 villages with the largest percentage of poor people. The results show that in some villages in the watershed, there has been a program of PNPM (National Community Empowerment Program) aimed at reducing the poverty of the community. But in the implementation of this program has not touched the community on all groups, so that the effectiveness of community empowerment has not been seen. Women with an amount equal to the number of men have not shown any meaningful involvement. The purpose of this research are: (1) to study the pattern and conception of poverty that happened in rainy season in Ngawi Regency; (2) to examine the role of women in poverty alleviation in the rainy season in Ngawi District. Data collection in this study with the sample method in 5 districts in the District Ngawi. Methods were performed with family samples, through questionnaires and face to face interviews with observation units were the head of the family. The results showed that the pattern and conception of poverty that occurs in the rainy season is quite varied, from the form of relative poverty to culture can be found in the life of the community. The role of women in efforts to eradicate poverty in the rainy season has not been optimal yet, due to the limited quality of human resources and the inherent social status in which women are more engaged in domestic work.